Konsep Waktu Sholat 5 Waktu Secara Astronomi - Rendy Febiansyah; Rara Azzahra (Jurnal Pelita Nusantara, 2025)
Determining the beginning of prayer times in the Islamic tradition is essentially a process of translating empirical natural phenomena mandated by sacred texts into highly precise mathematical and astronomical formulations. This research report comprehensively analyzes the astronomical scientific foundations of determining the five obligatory prayer times, with the main objective of bridging classical qualitative visual observation (rukyat) with contemporary astronomical computation systems (hisab). The fundamental problem addressed in this study is how to convert textual phenomena such as the sun crossing the meridian, the length of projected shadows, the setting of the solar disk, the disappearance of the twilight glow (syafaq), and the rising of the true dawn (fajr shadiq) into exact celestial spherical coordinate system parameters. Through a qualitative research method with an astronomical computation approach referring to the principles of Spherical Trigonometry and Jean Meeus's algorithms, this report outlines every determining variable: solar declination, Equation of Time, geographical latitude, and atmospheric correction factors (refraction, dip of the horizon, and semi-diameter). The research results show that all the intents of fiqh jurisprudence ultimately rely on one main variable: the altitude or depression angle of the sun ($h$). In addition to presenting an actual simulation for the Pontianak region, this report discusses the harmonious synthesis between fiqh and astronomy, the debate on dawn angle criteria among authorities in Indonesia, and the philosophical-legal foundation for determining the safety time value (ihtiyat). The main conclusion asserts that astronomy does not change the substance of sharia; rather, it provides absolute mathematical certainty to worship commands that are cosmological, natural, and universal.